2015
DOI: 10.13075/ijomeh.1896.00183
|View full text |Cite
|
Sign up to set email alerts
|

Dental awareness and oral health of pregnant women in Poland

Abstract: Objectives: The level of dental awareness of a pregnant woman affects the sanitary condition of her own teeth and the health of the child to be born. Poor oral health is considered to be a probable risk factor for the pre-term birth or low birth weight. The aim of this work was to assess the level of oral health knowledge that determines oral health condition of pregnant women in Poland. Material and Methods: Empirical data were obtained from the National Monitoring of Oral Health and Its Determinants, finance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
38
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 11 publications
4
38
0
11
Order By: Relevance
“…Likewise, a significant association between referred oral health state among pregnant women and general knowledge about oral health (p = 0.012) was found. These results also match with the investigations carried out by Gaszynska et al [31] and Boggess et al [32]. The same happens between referred oral health state and level of education among pregnant women, as shown in other investigations [24,27,29].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Likewise, a significant association between referred oral health state among pregnant women and general knowledge about oral health (p = 0.012) was found. These results also match with the investigations carried out by Gaszynska et al [31] and Boggess et al [32]. The same happens between referred oral health state and level of education among pregnant women, as shown in other investigations [24,27,29].…”
Section: Discussionsupporting
confidence: 92%
“…In the study by Martínez-Beneyto et al [24], the level of perceived oral health was grouped into excellent, very good, good, and poor, with a predominance of the good level (64.7%), comparable to the medium level of our study and therefore, there is also a coincidence with the present study. On the other hand, in the study by Gaszynska et al [31] (Poland, 2015), the state of oral health prevailed as medium (59.6%), followed by good (25%), and finally 14.7% considered it bad. However, this does not coincide with the studies by Aguilar-Cordero et al [25], Avula et al [27], and Bogges et al [32] (United States, 2010), where a predominance of the good level was observed.…”
Section: Discussionmentioning
confidence: 90%
“…Sebuah korelasi positif juga ditemukan pada penelitian di Polandia dimana Ibu hamil dengan pengetahuan kesehatan gigi mulut yang memadai, tidak memiliki masalah atau keluhan mengenai kesehatan gigi mulut mereka. 13 Kesadaran akan Pentingnya Kesehatan Gigi Mulut yang rendah menghasilkan status kesehatan mulut yang buruk dari subjek penelitian. 13 Dari penelitian ini didapat hubungan positif antara keluhan atau masalah kesehatan gigi mulut ibu hamil dengan kunjungan ke dokter gigi pada ibu hamil di wilayah kerja Puskesmas Serpong.…”
Section: Pembahasanunclassified
“…13 Kesadaran akan Pentingnya Kesehatan Gigi Mulut yang rendah menghasilkan status kesehatan mulut yang buruk dari subjek penelitian. 13 Dari penelitian ini didapat hubungan positif antara keluhan atau masalah kesehatan gigi mulut ibu hamil dengan kunjungan ke dokter gigi pada ibu hamil di wilayah kerja Puskesmas Serpong. Hal ini sejalan dengan Penelitian Chung dkk di California bahwa ibu hamil yang berkunjung ke Dokter Gigi lebih dari 6 bulan yang lalu memiliki status kesehatan gigi yang lebih buruk (ditandai dengan BOP, PI dan DMF-T yang lebih tinggi).…”
Section: Pembahasanunclassified
“…Study done in Baghdad revealed a higher caries experience (DMFS) among pregnant women compared to non-pregnant group but with no statistically significant difference. Caries experience (DMFS) showed a highly significant difference with pregnant educational level [7,12]. The compromised functional status, physical confinement, medical condition and cognitive impairment of significant numbers of women have important implications for oral health risks and dental treatment, in addition there are a variety of economic, social, psychological and behavioural factors which place pregnant women at risk for developing oral diseases [11].…”
Section: Introductionmentioning
confidence: 99%